Increased Serum Levels of Tumor Necrosis Factor-Alpha, Resistin, and Visfatin in the Children with Autism Spectrum Disorders: A Case-Control Study - Mohammad Ali Ghaffari; Elham Mousavinejad; Forough Riahi; Masoumeh Mousavinejad; Mohammad Reza Afsharmanesh (Neurology Research International)
Background. Autism spectrum disorders (ASDs) are complex disorders where the pathogenesis is not fully understood. Several proinflammatory and immunoinflammatory disturbances have been observed in the etiology of ASD. There is, however, limited knowledge on variations of adipokines in ASD. The present study aimed to analyze the serum levels of resistin, visfatin, and tumor necrosis factor-alpha (TNF-α) in children with ASD in relation to body weight, gender, and ASD severity level. Method. In total, 30 children with ASD (mean age: 7.72±2.65 y; range; 4–12 y) and 30 healthy children (mean age: 8.4±2.66 y; range: 4–12 y), including males and females, were matched for age, gender, and body mass index (BMI). Serum samples were collected, and visfatin, resistin, and TNF-α serum levels were measured using an enzyme-linked immunosorbent assay (ELISA) kit. Result. Serum visfatin, resistin, and TNF-α levels in children with ASD were significantly higher than that in the healthy patients (p<0.05). Two significant correlations were found: a correlation between resistin and visfatin with TNF-α in children with ASD (R = 0.8 and R = 0.62, resp.) and a correlation between resistin and visfatin in children with ASD (R = 0.66). Conclusion. Higher TNF-α, resistin, and visfatin levels were found in children with ASD in comparison with controls, suggesting that elevated levels of serum proinflammatory agents may be implicated in the pathophysiology of ASD.